Unbundling the housing crisis - Jay H. Isenberg (Oz, 2010)
Problem statement: An unregulated globalized residential mortgage industry imploded upon itself and transformed traditional neighborhood fabrics and ex-urban development tracts into widespread landscapes of mass foreclosures affecting society and our economy across all social strata to a critical point of near institutional financial collapse.